Relationship between body image and nutritional status of university students - Silva, Luanda Raquel Alcantara; Mendes, Renata Cristina Machado; Vasconcelos, Thais Meirelles de; Arruda, Soraia Pinheiro Machado; Bezerra, Ilana Nogueira (Revista de Psicología, 2021)
The aim of the study was to evaluate the perception and satisfaction of body image of university students and the association with nutritional status. Cross-sectional study, carried out with university students of both sexes, enrolled in health courses, in the city of Fortaleza, Ceará. A questionnaire was applied with questions related to gender, age, race / skin colour, family income, physical activity and image evaluation. Weight, height, waist circumference and hip circumference were measured. The weight condition was classified based on the Body Mass Index and Waist-Hip Ratio. Body image was investigated using the Adult Silhouettes Scale and for the assessment of body distortion, the values of the "current" and real body mass index were used. Pearson’s Chi-square tests and Poisson regression were used to assess possible associations between variables (p < 0.05). Of the 388 university students, 15.2% were satisfied with their body image and 77.3% showed distortion, 33.5% wanted to be bigger and 51.3% wanted to be smaller than they appeared. College students had a high prevalence of distortion (77.3%) and dissatisfaction (84.8%) with their body image. Overweight and abdominal obesity were associated with both distortion and dissatis-faction with body image. Dissatisfaction and distortion of body image are associated with the nutritional status of university students, being more evident in females.